Two-Dimensional Penta-NiPS Sheets: Two Stable Polymorphs - Dabsamut, Klichchupong; Thanasarnsurapong, Thanasee; Chatratin, Intuon; Maluangnont, Tosapol; Jungthawan, Sirichok; Boonchun, Adisak (My University, 2022)
The discovery of new and stable two-dimensional (2D) materials with exotic properties is essential for technological advancement. Inspired by the recently reported penta-PdPSe, we proposed penta-NiPS as a new member of the penta-2D materials based on first-principles calculations. The penta-NiPS monolayer is stable in two polymorphs including the α phase with an identical structure as penta-PdPSe and the newly proposed β phase with rotated sublayers. Comprehensive analyses indicated that both phases are thermodynamically, dynamically, mechanically, and thermally stable. The penta-NiPS is a soft material with 2D Young's modulus of Ea= 208 N m-1and Eb= 178 N m-1for the α phase and Ea= 184 N m-1and Eb= 140 N m-1for the β phase. Interestingly, the α-penta-NiPS showed nearly zero Poisson's ratios along the in-plane direction, where its dimensions would be maintained when being extended. For electronic application, we demonstrated that penta-NiPS is a wide band gap semiconductor with an indirect band gap of 2.35 eV for the α phase and 2.20 eV for the β phase.